Assesment of endocrinal and biochemical entities through liquid chromatography-tandem mass spectrometry/mass spectrometer: Inter-relative investigation of the interaction based cardiovascular formulation - Rakesh Das; Tapan Kumar Pal (Wolters Kluwer Medknow Publications, 2015)
Background: Combinatory oral dosage treatment of atorvastatin (ATVS) and olmesartan (OLM) drugs to cardiovascular patients reflects unpredicted results instead of its individual therapy, which was accessed on quantification of endocrinal and biochemicals of plasma through liquid chromatography-tandem mass spectrometry/mass spectrometer (LCMS/MS). Objective: Mission was to track the remarkable biochemical variation in the plasma after induction of the combined formulation, to evaluate the pharma-market rumor on its efficiency. Methods: To fulfil undergoing research objectives for digging-up of market insult, human patient volunteers were chosen according to the required criteria along with bioethical regulation. A sensitive, rapid and precise method was developed and validated to estimate aldosterone (ALD), angiotensin (ANG-II) and the Mevalonate (MVA) not Mevalonic acid through LCMS/MS over least samples of cardiovascular patients. Level of each endogenous biochemicals were determined in three stages - without drugs, with a single drug (OLM/ATVS) and with their combination that was then correlate with blood pressure of respective volunteers. Result and Discussion: Comparative and correlative studies panaroma among these analytes was detected. The selectivity, specificity, linearity, precision, accuracy, extraction recovery, limit of detection and limit of quantification, stability were the essential points of validation of the developed methodology. And the significance of each endogenous analyte data were based on P ≥ 0.001. Thus, low value of ALD and reciprocally higher in ANG-II on administered single drug than its combination and equal concentration of mevalonate in both stages, was discovered. Conclusion: This concludes that the cardiovascular dosage formulation entrenched in the market are not synergistic and effective compared with a single drug as antihypertensive drug.